On tact, & the made up world - Glazer, Michèle, 1958- (Kuhl House poets., 2010)
Michele Glazer's poems take on questions of being and value, exploring not just what is, but how it is. The poems trouble borders - between self and other, old and young, sick and well, stranger and intimate; between physical states in processes of decay; and between line and phrase, sentence and interruption, prose and poem, resisting the desire for something irrefutable with an abiding skepticism. The poems are drawn to missteps in perception and in language, those fractures that promise to crack open a surface to yield some other, greater meaning: "What is looke